Integrating transcription and splicing into cell fate: Transcription factors on the block. (28th July 2022) - Boumpas, Panagiotis; Merabet, Samir; Carnesecchi, Julie
Abstract: Transcription factors (TFs) are present in all life forms and conserved across great evolutionary distances in eukaryotes. From yeast to complex multicellular organisms, they are pivotal players of cell fate decision by orchestrating gene expression at diverse molecular layers. Notably, TFs fine‐tune gene expression by coordinating RNA fate at both the expression and splicing levels. They regulate alternative splicing, an essential mechanism for cell plasticity, allowing the production of many mRNA and protein isoforms in precise cell and tissue contexts. Despite this apparent role in splicing, how TFs integrate transcription and splicing to ultimately orchestrate diverse cell functions and cell fate decisions remains puzzling. We depict substantial studies in various model organisms underlining the key role of TFs in alternative splicing for promoting tissue‐specific functions and cell fate. Furthermore, we emphasize recent advances describing the molecular link between the transcriptional and splicing activities of TFs. As TFs can bind both DNA and/or RNA to regulate transcription and splicing, we further discuss their flexibility and compatibility for DNA and RNA substrates. Finally, we propose several models integrating transcription and splicing activities of TFs in the coordination and diversification of cell and tissue identities. This article is categorized under: RNA Processing > Splicing Regulation/Alternative Splicing RNA Interactions with Proteins and Other Molecules > Protein‐RNA Interactions: Functional Implications RNA Processing > Splicing Mechanisms Abstract : Transcription factors (TFs) are key players of gene expression integrating transcription and splicing. Their activity is orchestrated by multiple features such as DNA/RNA‐binding affinity and co‐regulatory proteins, altogether fine‐tuned by the local nuclear environment.